Correction: Identification of deleterious variants in patients with male infertility due to idiopathic non-obstructive azoospermia - Dongdong Tang; Kuokuo Li; Hao Geng; Chuan Xu; Mingrong Lv; Yang Gao; Guanxiong Wang; Hui Yu; Zhongmei Shao; Qunshan Shen; Hui Jiang; Xiansheng Zhang; et al. (BMC, 2022)
An amendment to this paper has been published and can be accessed via the original article.